Revitalization of Environmental Aesthetics Through Mural Activities at the RT Community Hall of Kampung Deles IV, Surabaya - Josephine Roosandriantini; Anas Hidayat; Yohanes Kristianus Harianto; Sultan Agni Setyawan; Jason Rivaldy Tanaya; Widriyakara Setiadi (Talenta Publisher, 2026)
Environmental aesthetic revitalization is a crucial effort in creating a comfortable, green, and functional public space for the community. Mural art, as a form of visual expression, holds great potential in beautifying the environment and reinforcing local identity. This community service program was conducted at the RT Hall of Kampung Deles IV, Surabaya, an area experiencing visual degradation due to dull and poorly maintained walls. Through a participatory approach, the service team and local residents collaboratively planned, designed, and implemented mural artworks that highlight local wisdom and communal values. The results showed significant improvement in environmental aesthetics, a strengthened sense of belonging among residents, and increased motivation to maintain the RT hall as a hub for social activities. This project demonstrates that mural art can serve as an effective medium for community-based empowerment and environmental revitalization.